Substitutions at position 263 within the von Willebrand factor type A domain determine the functionality of complement C2 protein - Kuźniewska, Alicja; Thiel, Marcel; Kowalska, Daria; Felberg-Miętka, Anna; Szynkowski, Patryk; Ołdziej, Stanisław; Arjona, Emilia; Jongerius, Ilse; Rodriguez de Córdoba, Santiago; Okrój, Marcin; Urban, Aleksandra (Frontiers in Immunology, 2022)
The complement system is one of the first defense lines protecting from invading pathogens. However, it may turn offensive to the body’s own cells and tissues when deregulated by the presence of rare genetic variants that impair physiological regulation and/or provoke abnormal activity of key enzymatic components. Factor B and complement C2 are examples of paralogs engaged in the alternative and classical/lectin complement pathway, respectively. Pathogenic mutations in the von Willebrand factor A domain (vWA) of FB have been known for years. Despite substantial homology between two proteins and the demonstration that certain substitutions in FB translated to C2 result in analogous phenotype, there was a limited number of reports on pathogenic C2 variants in patients. Recently, we studied a cohort of patients suffering from rare kidney diseases and confirmed the existence of two gain-of-function and three loss-of-function mutations within the C2 gene sequences coding for the vWA domain (amino acids 254-452) or nearly located unstructured region (243-253) of C2 protein. Herein, we report the functional consequences of amino acid substitution of glutamine at position 263. The p.Q263G variant resulted in the gain-of-function phenotype, similarly to a homologous mutation p.D279G in FB. Conversely, the p.Q263P variant found in a patient with C3 glomerulopathy resulted in the loss of C2 function. Our results confirm that the N-terminal part of the vWA domain is a hot spot crucial for the complement C2 function.